2014
DOI: 10.1063/1.4868512
|View full text |Cite
|
Sign up to set email alerts
|

Note: Limitations of the optoelectronic control for carbon nanoparticles synthesis via arc-discharge in solution

Abstract: Submerged electric arc discharge in liquids has shown to be a promising method for synthesizing a wide variety of nanomaterials. However, it requires an accurate current stability control to ensure the desired purity and structure of the products. The discharge stability control through light emission has been previously studied, but still requires further investigation to clarify the influence of some parameters. The present work has studied the solution's transmittance variation over time, the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Ref. [53] revealed that α does not obey a flat behavior because it may be awaited for isotropic emission. In the 30-50 A current range, the electrode gap is small (~0.7-1 mm), and the anode spot rapidly moves all over the anode front end surface as it wears out (Figure 9(a)).…”
Section: Merits and Disadvantages Of The Stabilization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [53] revealed that α does not obey a flat behavior because it may be awaited for isotropic emission. In the 30-50 A current range, the electrode gap is small (~0.7-1 mm), and the anode spot rapidly moves all over the anode front end surface as it wears out (Figure 9(a)).…”
Section: Merits and Disadvantages Of The Stabilization Methodsmentioning
confidence: 99%
“…The fulfilment of these four requirements in a water SAD was evaluated in [53], identifying several limitations of optoelectronic control. A Teflon ring, which was coaxially positioned with the electrodes and holding eight radial fixed and uniformly distributed optical fibers, was placed around the arc zone (Figure 6(b)).…”
Section: Sad Without Any Control Techniquementioning
confidence: 99%
“…The voltage applied to the electrodes was measured from the anode holder disregarding the voltage drop at the shunt. The other three analog inputs are free to use for experimental purposes as in [5].…”
Section: Methodsmentioning
confidence: 99%
“…The optoelectronic control has several limitations as reported in [5]. In regards to the second approach [6], according to a typical arc voltage/current characteristic, in its hissing part (where the thermal ionization is present and the nanoparticles are formed), the voltage variation is very small in comparison to its corresponding current variation (dU/dI ≈ 0), thus making less sensitive the control.…”
Section: Automated System For the Synthesis Of Nanostructures Via Arc...mentioning
confidence: 99%
“…In almost all published works on SADW, appropriate systems for arc stabilisation are not used [10]. In most studies, arc stability evaluation is based solely on the intensity of emitted arc light or other unsuitable indicators [11]. Additionally, the MWCNTs and CNOs produced via SADW are accompanied by other CNSs and impurities with similar structures.…”
Section: Introductionmentioning
confidence: 99%